PENGARUH ELECTRONIC WORD OF MOUTH DI SOSIAL MEDIA INSTAGRAM TERHADAP CITRA DESTINASI WISATA DAN NIAT BERKUNJUNG KE PULAU LOMBOK - Ardiyanti, Baiq Novita (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this study is to examine the influence of electronic word of mouth on Instagram (a social media) on the image of tourism destination and the intention to travel to Lombok Island. The population of this study is Indonesian tourist who are active users of Instagram who have never visit Lombok Island. The sample of this study was selected  through purposive  sampling  technique.  Online  survey  was  conducted on  a sample of 160 respondents. The data were analyzed through descriptive analysis and Partial Least Square (PLS) using 3.0 SmartPLS.The result of this study indicates that electronic word of mouth has a positive effect on improving the image of tourism destination and creating the intention to travel and that image of tourism destination has a positive effect on creating the intention to travel.Keywords : Electronic Word of Mouth, Image of Tourism Destination, Intention to Travel